2020
DOI: 10.1111/jfpe.13571
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drying temperature on drying kinetics, energy consumption, bioactive compounds and cooking quality of pasta enriched with spinach

Abstract: The influence of drying temperature on drying kinetics, energy consumption, bioactive compounds, and cooking quality of the pasta enriched with spinach was studied. Pasta enriched with spinach were dried at 35, 45, 55, 65 and 75 C. The drying kinetics, energy consumption, water activity, moisture content, total carotenoids, antioxidant activity, total chlorophyll, total phenolic, hardness, and cooking quality parameters were evaluated. Mathematical models were fitted to predict the drying kinetics, energy cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Pasta quality depends mainly on the ingredients used for its preparation. The method of production (lamination or extrusion) [17,18], dough mixing process, and drying conditions also have a significant influence on pasta properties [19].…”
Section: Introductionmentioning
confidence: 99%
“…Pasta quality depends mainly on the ingredients used for its preparation. The method of production (lamination or extrusion) [17,18], dough mixing process, and drying conditions also have a significant influence on pasta properties [19].…”
Section: Introductionmentioning
confidence: 99%
“…Three different temperature levels, 40, 50 and 60°C were applied during the drying process of PCD leaves while the concentration of ethanol and extraction temperature were kept constant at 50% (v/v) and 70°C, respectively during extraction of GA from dried leaves. The levels of drying temperature used in this study were selected based on the literature where the authors have reported that drying at above 70°C was detrimental to the bioactive properties and temperature up to 60°C retained most of the bioactive compounds 40,41 . The best drying temperature was chosen based on the color L*a*b* and GA content of dried leaves.…”
Section: Methodsmentioning
confidence: 99%
“…The cooking time (CT) was directly affected by CHMD parameters MPD and T; and varied between 9.5 and 13.5 min for the lowest (1.33 W/g, 40°C) and the highest (2.0 W/g, 70°C) levels of MPD and T. During cooking, the BGN slowly absorbs water and begins to swell. The protein-starch matrix is responsible for the physical integrity of the BGN during cooking (Vimercati et al, 2020). Figure 5d depicts the response surface graphs to show the effect of MPD and T on the cooking time of dried BGN.…”
Section: Effect On the Cooking Timementioning
confidence: 99%